Student-led Classroom: Review on the advantages and disadvantages - Shaki, Ummi Habibah Mohd; Shakil, Nurul Syifaa Mohd (Journal of Accounting, Business and Management (JABM), 2024)
This paper examines the benefits and drawbacks of student-led classrooms within the context of constructivist learning theory. The principles of constructivism align with this educational approach, which emphasizes active participation, social interaction, and contextual learning. The study investigates the influence of student-led classrooms on factors such as engagement, critical thinking, and knowledge retention. Although constructivist approaches, such as problem-based and inquiry-based learning, have notable advantages, they also pose difficulties, such as the requirement for explicit instruction and resource intensity. The study examines existing literature on the efficacy of student-led classrooms and asynchronous online discussion forums (AODFs), providing valuable insights into techniques that improve student engagement and learning outcomes.